2002
DOI: 10.1152/ajpregu.00238.2001
|View full text |Cite
|
Sign up to set email alerts
|

Lipid oxidation fuels recovery from exhaustive exercise in white muscle of rainbow trout

Abstract: . Lipid oxidation fuels recovery from exhaustive exercise in white muscle of rainbow trout. Am J Physiol Regulatory Integrative Comp Physiol 282: R89-R99, 2002; 10.1152/ajpregu.00238.2001.-The oxidative utilization of lipid and carbohydrate was examined in white muscle of rainbow trout (Oncorhynchus mykiss) at rest, immediately after exhaustive exercise, and for 32-h recovery. In addition to creatine phosphate and glycolysis fueling exhaustive exercise, near maximal activation of pyruvate dehydrogenase (PDH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 38 publications
3
77
1
5
Order By: Relevance
“…Therefore, fish muscle is particularly dependent on fat stores to support endurance swimming. Lipid oxidation also plays an important role after swimming to exhaustion, when it provides most of the ATP for white muscle recovery (Richards et al, 2002). Early work on the lipid kinetics of rainbow trout shows that the mobilization of fat reserves [or lipolysis measured as the rate of appearance of glycerol (R a glycerol)] and fatty acid fluxes are not stimulated by submaximal exercise like they are in mammals, even when swimming lasts for several days (Fig.…”
Section: Lipid Kinetics: Lipoproteins As a Fuel For Musclementioning
confidence: 99%
“…Therefore, fish muscle is particularly dependent on fat stores to support endurance swimming. Lipid oxidation also plays an important role after swimming to exhaustion, when it provides most of the ATP for white muscle recovery (Richards et al, 2002). Early work on the lipid kinetics of rainbow trout shows that the mobilization of fat reserves [or lipolysis measured as the rate of appearance of glycerol (R a glycerol)] and fatty acid fluxes are not stimulated by submaximal exercise like they are in mammals, even when swimming lasts for several days (Fig.…”
Section: Lipid Kinetics: Lipoproteins As a Fuel For Musclementioning
confidence: 99%
“…Alevins that develop towards an exogenous nutritional may THE JOURNAL OF EXPERIMENTAL BIOLOGY 1606 thus, through this molecular pathway, favour deposition of lipids, which has been observed in trout alevins following first feeding (F.M., unpublished data) and in the muscle of juvenile trout (Fauconneau et al, 1997). In adult trout, these stores will later fulfill metabolic demands during fasting (Jezierska et al, 1982) and exercise (Richards et al, 2002), and also play a role in cold acclimatization (Egginton et al, 2000). In order to substantiate the potential role of omy-miRNA-143 as a potential marker for the process of lipid deposition during ontogenesis, we equally investigated the expression of cd36, a fatty acid transporter with a rate-limiting function on triglyceride synthesis in adipocytes and muscle (Coburn et al, 2001; Christiaens et al, 2012), which in rainbow trout has been identified as a marker for muscular lipid deposition (Kolditz et al, 2010).…”
mentioning
confidence: 91%
“…Milligan, 1996;Richards et al, 2002a;Richards et al, 2002b). At exhaustion, glycogen, adenosine 5Ј-triphosphate (ATP) and phosphocreatine (PCr) stores in working muscle are reduced and lactate and H + levels are elevated (Richards et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…The current model for the restoration of muscle energy reserves in fish after exhaustive exercise suggests that in adult fish glycogen is resynthesized in situ with lactate as the main substrate (Milligan and Girard, 1993;Wang et al, 1997;Richards et al, 2002a). Glucose, the main glycogenic substrate in mammalian muscle, is probably not an important glycogenic or oxidative substrate for trout white muscle since muscle has low hexokinase activity (Knox et al, 1980;Storey, 1991) and the expression of glucose transporters in the muscle membrane is extremely low and their physiological role is unclear (Legate et al, 2001;Teerijoki et al, 2001;Capilla et al, 2002).…”
Section: Introductionmentioning
confidence: 99%